Novel pathogenic variants underlie SLC26A4-related hearing loss in a multiethnic cohort. (October 2017) - Cengiz, Filiz Basak; Yilmazer, Rasim; Olgun, Levent; Sennaroglu, Levent; Kirazli, Tayfun; Alper, Hudaver; Olgun, Yuksel; Incesulu, Armagan; Atik, Tahir; Huesca-Hernandez, Fabiola; Domínguez-Aburto, Juan; González-Rosado, Garly; et al.
Abstract: Objectives: The genetics of sensorineural hearing loss is characterized by a high degree of heterogeneity. Despite this heterogeneity, DNA variants found within SLC26A4 have been reported to be the second most common contributor after those of GJB2 in many populations. Methods: Whole exome sequencing and/or Sanger sequencing of SLC26A4 in 117 individuals with sensorineural hearing loss with or without inner ear anomalies but not with goiter from Turkey, Iran, and Mexico were performed. Results: We identified 27 unique SLC26A4 variants in 31 probands. The variants c.1673A > G (p.N558S), c.1708-1G > A, c.1952C > T (p.P651L), and c.2090-1G > A have not been previously reported. The p.N558S variant was detected in two unrelated Mexican families. Conclusion: A range of SLC26A4 variants without a common recurrent mutation underlies SLC26A4 -related hearing loss in Turkey, Iran, and Mexico.